New Imadazopyrazines with CDK9 Inhibitory Activity as Anticancer and Antiviral: Synthesis, In Silico, and In Vitro Evaluation Approaches - Aisha A. Alsfouk; Hanan M. Alshibl; Najla A. Altwaijry; Ashwag Alanazi; Omkulthom AlKamaly; Ahlam Sultan; Bshra A. Alsfouk (MDPI AG, 2023)
This study describes the synthesis and biological activity of new imadazopyrazines as first-in-class CDK9 inhibitors. The inhibition of CDK9 is a well-established therapeutic target in cancer therapy. The new compounds were assessed using an in vitro kinase assay against CDK9. In this assay, compound 1d exhibited the highest CDK9 inhibition with an IC50 of 0.18 µM. The cytotoxicity effect of the novel compounds was evaluated in three cancer cell lines: HCT116, K652, and MCF7. The results of this assay showed a correlation between the antiproliferative effect of the inhibitors and their CDK9 inhibitory effect in the biochemical assay. This suggests CDK9 inhibition as a mechanistic pathway for their anticancer effect. Several compounds demonstrated potent cytotoxic effects with single-digit micromolar IC50 values yielded through an MTT assay. The compounds with the most promising data were further assessed for their antiviral activity against human Coronavirus 229E. The results showed that compound 4a showed the highest antiviral potency with an IC50 of 63.28 µM and a selectivity index of 4.8. In silico target prediction data showed that 4a displayed a good affinity to proteases. The result of the docking studies of 4a with COVID-19 main protease revealed a high binding affinity, which confirmed the results obtained from in vitro study. The physiochemical and in silico pharmacokinetic parameters indicated reasonable drug-likeness properties of the new compounds, including solubility, lipophilicity, absorption, oral bioavailability, and metabolic stability. Further lead optimization of this novel scaffold could lead to a revolution of a new class of preclinical CDK9 agents.